Crystal structure of S-methyl ß-N-(methylacetyl)methylene-dithiocarbazate, C6H10N2OS2 - Tarafder, M. T. H.; Saravanan, N.; Crouse, Karen Anne; Yamin, B. M.; Fun, H. K.; Raj, S. S. S.; Razak, I. A. (Oldenbourg Wissenschaftsverlag, 2001)
CoH10N2OS2, monoclinic, P12(1)/n(1) (No. 14), a = 1.2699(1) Angstrom, b= 13.7534(2) Angstrom, c = 15.8'80(4) Angstrom, beta = 97.263(1)degrees, V = 922.1 Angstrom (3), 2 = 4, R(F) = 0.063, w(Ref)(F-2) = 0.173, T = 293 K.